Recent Advances in the Pharmacological Treatment of Pervasive Developmental Disorders - Moussavand, Samareh; Findling, Robert L. (Current Pediatric Reviews, 2007)
Introduction. There is growing body of evidence to suggest that pharmacotherapy may be a rational form of intervention for some patients with pervasive developmental disorders (PDDs). The purpose of this article is to describe what is known about medication treatment for these patients. Methods. Published papers regarding the pharmacotherapy of PDDs were collected and reviewed. For each study, particular attention was paid to ascertaining patient characteristics, the medication doses employed, and medication tolerability. Results. There is evidence of varying methodological rigor to suggest that several medications may have a role in the treatment of patients with PDDs. However, to date, few randomized double-blind treatment studies have been published. In addition, there is very little known about the long-term safety of many of these agents in this patient population. Conclusions. Some patients with PDDs may benefit acutely from pharmacotherapy. Many marketed psychotropic agents that putatively hold promise for these patients have not been rigorously studied. More short-term and long-term research regarding the pharmacotherapy of patients with PDDs is needed.
Keywords: atypical antipsychotics